2013
DOI: 10.1175/mwr-d-12-00321.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Orographic Precipitation around the Meghalaya Plateau Associated with Intraseasonal Oscillation and the Diurnal Cycle

Abstract: Mesoscale processes that cause tremendous amounts of precipitation around the Meghalaya Plateau, northeast India, were investigated using a regional atmospheric model, with a particular focus on the possible role of an intraseasonal oscillation (ISO) and the diurnal cycle. A numerical experiment was conducted using the Weather Research and Forecasting Model (WRF) to simulate a prominent submonthly-scale ISO event observed during June-July 2004. A WRF experiment successfully simulated the timing and magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Diurnal variation is also a dominant fluctuation in rainfall/convection around the MBWM (Ohsawa et al 2001;Hirose et al 2008;Takahashi et al 2010;Biasutti et al 2012). The relationship between the submonthlyscale ISO and diurnal variation has been presented in previous studies that analyzed a single year (e.g., Ohsawa et al 2000;Terao et al 2006;Sato 2013). Sato (2013) pointed out the importance of the nocturnal low-level jet (LLJ) appearing around 900 hPa for enhancing orographic rainfall around the Meghalaya Plateau.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Diurnal variation is also a dominant fluctuation in rainfall/convection around the MBWM (Ohsawa et al 2001;Hirose et al 2008;Takahashi et al 2010;Biasutti et al 2012). The relationship between the submonthlyscale ISO and diurnal variation has been presented in previous studies that analyzed a single year (e.g., Ohsawa et al 2000;Terao et al 2006;Sato 2013). Sato (2013) pointed out the importance of the nocturnal low-level jet (LLJ) appearing around 900 hPa for enhancing orographic rainfall around the Meghalaya Plateau.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, low-level atmosphere exhibits slightly stronger convective instability on peak break days than on peak active days. Recently, Sato (2013) pointed out that the intensity of southerly/southwesterly low-level wind around 900 hPa is a crucial factor in heavy precipitation around the Meghalaya Plateau during the active period of submonthly-scale ISO because stronger low-level wind is sufficient to overcome the vertical stratification barrier and can reach the lifting condensation level. At latitudes of 20.5-21.5°N, a strong southwesterly low-level wind is dominant over the head of the Bay of Bengal in the active phase (Fig.…”
Section: Detailed Rainfall Distribution and Its Time Evolutionmentioning
confidence: 99%
“…The use of a weather research and forecasting regional model revealed that the strong southwesterly winds in the lower troposphere transport moisture which triggers forced lifting and brings orographic rainfall to the southern slope of the Meghalaya Hills during the active period of quasi-biweekly oscillation, as observed also by the TRMM (Sato 2013). Moreover, the low-level jet appearing at 900 hPa accelerates the preexisting southwesterly flow and is responsible for the evening to early morning maximum of rainfall.…”
Section: Propagation Of the High Rainfallmentioning
confidence: 88%
“…Furthermore, we should pay attention to whether the spatial resolution can resolve the horizontal resolution of each cumulus convection cell, as shown in Sato et al (2008). For example, Kataoka and Satomura (2005) and Sato (2013) successfully simulated nighttime precipitation events during the mature monsoon season in this region in experiments using spatial resolutions of 2.0 and 3.6 km, respectively. As shown by these previous simulations, experiments with a spatial resolution finer than 5 km can be expected to improve the simulated nighttime precipitation during the mature monsoon season…”
Section: Precipitation Frequency During the Mature Monsoon Seasonmentioning
confidence: 99%
“…Typically, there is also a well-defined diurnal variation in this region. Precipitation occurs during the afternoon and early morning over the southern plain in Bangladesh (Ohsawa et al 2001;Islam et al 2004;Terao et al 2008), whereas the southerly monsoon flow and low-level jet tend to generate nocturnal precipitation over the northern mountainous areas (Barros and Lang 2003;Kataoka and Satomura 2005;Terao et al 2006;Murata et al 2008;Sato 2013). These seasonal differences in precipitation over South Asia, together with the remarkable diurnal variations, allow us to evaluate the impact of CPs on precipitation simulations.…”
Section: Introductionmentioning
confidence: 99%